1994
DOI: 10.1002/acp.2350080505
|View full text |Cite
|
Sign up to set email alerts
|

Using elaborative interrogation to facilitate acquisition of factual information in cooperative learning settings: One good strategy deserves another

Abstract: The primary purpose of this study was to determine whether providing 6th-grade students with cooperative elaborative interrogation instruction would facilitate learning relative to providing them with cooperative learning, elaborative interrogation or reading-for-understanding instructions. All students were presented with 36 factual statements about six animals. Cooperative elaborative interrogation students were instructed to work collaboratively and use their prior knowledge to state why each fact is true. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1
2

Year Published

1995
1995
2009
2009

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 21 publications
1
8
1
2
Order By: Relevance
“…These students may have been unfamiliar with co-operative learning strategies (Johnson and Johnson, 1990Johnson, , 1991. In contrast to what was observed here, Kahl and Woloshyn (1994) demonstrated that small groups of students, who were trained in co-operative learning techniques, produce as many adequate responses as those who use elaborative interrogation independently, with this type of response being associated with greater learning than reading target information for understanding.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…These students may have been unfamiliar with co-operative learning strategies (Johnson and Johnson, 1990Johnson, , 1991. In contrast to what was observed here, Kahl and Woloshyn (1994) demonstrated that small groups of students, who were trained in co-operative learning techniques, produce as many adequate responses as those who use elaborative interrogation independently, with this type of response being associated with greater learning than reading target information for understanding.…”
Section: Discussioncontrasting
confidence: 50%
“…Kahl and Woloshyn, 1994;Wood et al, 1990), when students activated relevant background knowledge that supported target information, learning was enhanced relative to when they generated inadequate responses or failed to generate a response. Listening to a partner's adequate responses also facilitated learning relative to listening to their inadequate responses or response failures.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have measured the durability of the effectiveness of EI; however, those studies have concentrated primarily on recognition measures such as matching tasks (Kahl and Woloshyn 1994;Willoughby et al 1993), selection of true statements Woloshyn and Stockley 1995), and rating confidence of correct answers (Woloshyn and Stockley 1995). Further, texts used in all of the prior EI durability investigations presented to-be-learned sentences with corresponding elaborative interrogation prompts with each sentence.…”
Section: Methodsmentioning
confidence: 99%
“…De plus, l'apprentissage coopératif favorise le développement académique, interpersonnel et social des apprenants (Johnson et Johnson, 1990a ;Arcan, 2003). D'un autre côté, l'engagement actif des étudiantes et étudiants dans les activités coopératives en classe nécessite un enseignement explicite et concret des habiletés et des stratégies coopératives (Johnson et Johnson, 1990bJohnson, Johnson et Holubec, 1991, 1993aCooper et Mueck, 1990;Kahl et Woloshyn, 1994;Clarke et al, 1992;Howden, 1997et Arcand, 2003 Deux définitions (Garnier, 1991 ;Daniel, 1996) (Johnson et Johnson, 1994Johnson, Johnson et Holubec, 1991, 1993a …”
Section: -Hypothèse De Rechercheunclassified
“…Ils doivent planifier adéquatement leurs activités coopératives afin d'assurer la participation active et spontanée des apprenants. Us doivent aussi préparer leurs élèves à vivre pleinement l'expérience d'apprentissage coopératif et à en tirer des bénéfices en leur enseignant de façon spécifique des habiletés coopératives (Johnson et Johnson, 1990bJohnson, Johnson et Holubec, 1991, 1993aCooper et Mueck, 1990;Kahl et Woloshyn, 1994;Clarke et al, 1992;Howden, 1997et Arcand, 2003.…”
Section: : Les Aspects Pédagogiques De L'enseignement D'approche Coopunclassified